A Retrospective Audit of Widal Testing For Enteric Fever in the City Of Ahmedabad - Iyer, Veena; Sharma, Ayushi; Cottagiri, Susanna Abraham; Mahapatra, Subhransu; Purohit, Hitesh Raj; Vegad, Mahendra; Shah, Parul; Shah, Bhavini; Solanki, Bhavin; Soni, Sumeeta (Eastern Journal of Medical Sciences, 2018)
Introduction: Widal test has been used extensively for the sero-diagnosis of Enteric fever in India, however, its accuracy and reliability are debatable. We studied widal testing and widal positivity rates in the entire city of Ahmedabad for the diagnosis of Enteric Fever. Methods We screened all 1700 possible diagnostic laboratory facilities, in Ahmedabad, in the public and private sector. We performed telephonic surveys for the initial filtering of facilities that could be conducting widal testing. It was followed by physical visits to probable facilities to confirm testing methods and preservation of reports of widal testing. We followed a systematic process for screening and selection of 23 laboratories, which conducted widal tests and had reliable data. While 14 laboratories refused to share data, data provided by three of them were inappropriate and couldn’t be used. We finally analyzed data from four large public hospitals, one private trust hospital and one corporate laboratory for variable periods in a span of 15 years (2000 – 2015). Result: The Widal testing rate was found to be 8.7% and widal positivity as 12.5% in a sample of 1.2 million clinically suspected in-patients. In 15 years, the private hospital had admitted 1/10th as many cases as all the public hospitals together. However, the widal testing and positivity rates were similar in both. We observed a lower proportion of widal positivity among children below 12 years and a disproportionate, but insignificant, gender distribution of widal positivity. Conclusion: This study indicates that the widal test, which is meant to be an initial screening test, is widely used in the city. We propose linkage of testing and reporting of widal with other more reliable and accurate tests such as Typhidot and blood culture in order to strengthen our knowledge of enteric fever epidemiology in India.